The effectiveness of Self-care –training programs on promotion of the perceived stress in pre-eclampsia, A Clinical Trial study - Ahmadinezhad, Fatemeh; Taheri, Mina; Hasanzadeh, Fahimeh; Akbarzadeh, Marzieh (International Journal of Psychosocial Rehabilitation, 2020)
Objective: Preeclampsia is one of the causes of maternal and neonatal mortality in the world. Lifestyle changes in pregnant women with hypertension can prevent future risks for mother and fetus. The aim was the effectiveness of Self-care –training programs on promotion of the perceived stress in pre-eclampsia, A Clinical Trial study. Materials and Methods: This clinical trial study was performed on 96 pregnant women with preeclampsia (48 patients per group) in selected hospitals of Shiraz in 2018. The self-care education was conducted. The control group received only routine pregnancy cares. The self-care and perceived stress scores and the correlation between the two groups were assessed. Data were analyzed using t-test, Pearson correlation, Chi- square, Kolmogorov-Smirnov test. P-value of 0.05 was considered significant. Results: After intervention, the mean score of self-care in the intervention group was significantly higher than the control group (p